Economic and efficient multi-objective operation optimization of integrated energy system considering electro-thermal demand response. (15th August 2020) - Wang, Yongli; Ma, Yuze; Song, Fuhao; Ma, Yang; Qi, Chengyuan; Huang, Feifei; Xing, Juntai; Zhang, Fuwei
Abstract: Multi energy demand response is an important measure to achieve the economic and efficient operation of the integrated energy system (IES), which is of great significance to promote the sustainable development of the IES. The concept of demand response (DR) is extended to IES, and a double objective operation optimization model of IES considering integrated demand response (IDR) mechanism is proposed. Firstly, based on the electro-thermal IES, this paper proposes a demand response mechanism considering electric load and thermal load. According to the load composition (transferable load, reducible load, adjustable thermal load), the load management strategy is established. Then, based on the DR mechanism of electro-thermal IES, a multi-objective operation optimization model is established for the first time, which takes the economic benefits and comprehensive energy efficiency as the objective function. The model involves the equipment constraint in the process of energy production and energy transmission. The relationship between total operation cost and comprehensive energy efficiency of electro-thermal IES is analyzed in the part of Data, Simulation Results and Analysis. Finally, the results show that the model effectively improves the economic benefits and comprehensive energy efficiency of IES, and reduces the pollutants emissions to a certain extent. Highlights: The information and energy flow framework of an integrated energy system is proposed. An integrated demand response mechanism considering load composition is established. A dual objective operation optimization model of integrated energy system is established. The model aims at economy and comprehensive energy efficiency. The model can improve the economic, efficiency and environmental benefits of the system.